دراسة تحليلية لاتجاهات طلبة جامعة قاصدي مرباح بورقلة نحو السياحة العلمية - فرحي, نعيمة (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الورقة البحثية إلى تسليط الضوء على مفهوم السياحة العلمية باعتبارها شكلا من أشكال السياحة، والتي تستقطب أعدادا متزايدة من السياح الذين يبحثون عن التزود بالعلم والمعرفة كل سنة، إضافة إلى تحليل اتجاهات الطالبة الجامعيين نحو السياحة العلمية من خلال قياس اتجاهات عينة من طلبة جامعة قاصدي مرباح بورقلة تقدر ب322 طالبا . و من أهم النتائج التي توصلت اليها الدراسة أن هناك اتجاها متوسطا لطلبة جامعة قاصدي مرباح نحو السياحة العلمية، إضافة إلى وجود اختلاف في توجه الطلبة الذكور و الإناث نحو السياحة العلمية و كذا وجود اختلاف في توجهات الطلبة نحو السياحة العلمية حسب مستواهم الدراسي و حسب تخصصهم. كما تهدف هذه الدراسة إلى ابراز اهم العوامل التي تؤثر سلبا على توجه الطلبة نحو السياحة العلمية. This research paper aims to shed light on the concept of scientific tourism as a form of tourism, which attracts increasing numbers of tourists who seek to acquire knowledge every year, In addition it aims to analyzing the attitudes of university students towards scientific tourism by measuring the trends of a sample of 322 students from Kasdi Merbah University of Ouargla. One of the most important results of the study is that there is a middle attitude of students of Kasdi Merbah University towards scientific tourism. Besides, there is a difference in the attitudes of male and female students towards scientific tourism, as well as the presence of a difference in students’ attitudes towards scientific tourism according to their academic level and to their specialization. This study also aims to highlight the most important factors that negatively affect students' attitudes towards scientific tourism
An analytical study of the attitudes of the students of Kasdi Merbah University of Ouargla towards scientific tourism
مقال
Keywords: سياحة ; سياحة علمية ; اتجاهات الطلبة